"Grounded Theory Approaches in Business Studies: A Realistic Experiences" - Al-Ammar, Fahd; Al-Dhabib, Mishal (The Arab Journal of Administration, 2022)
Grounded theory has recently gained recognition within the context of business studies, due to its capability to provide real and comprehensive descriptions of organisations issues. However, researchers, especially beginners, may face different obstacles in applying grounded theory methodologies. Although much has been discussed in English business studies literature, these discussions may still confuse the researcher, which may lead to producing imperfect use of the grounded theory. Furthermore, a few researchers have reflected and documented their experiences in using and applying grounded theory, which creates a gap in Arabic business studies literature. By using two factual case studies, within the context of business studies, this paper attempts to reflect actual experiences and provides guidance to researchers, through clarifying some of the obstacles and steps involving the grounded theory process. This aims to assist researchers in using and applying the most appropriate forms of grounded theory in the field of business studies.